Solvent Extraction of Zn(II) from Aqueous Sulphate Media by Di(2-Ethylhexyl) Phosphoric Acid in Kerosene: Solvent Extraction of Zinc (Biological Sciences - PJSIR, 2009)
The extraction equilibrium studies of Zn(II) from sulphate medium by di(2-ethylhexyl) phosphoric acid (D2EHPA, H2A2) in kerosene revealed that the distribution ratio (D) decreased with the increase of initial [Zn(II)] in the aqueous phase and increased with the increase of equilibrium pH and extractant concentration. The equilibration is reached within 2 min. The species extracted into the organic phase is thought to be ZnA2.HA. The pH and extractant dependencies were about 2 and 1.67, respectively. The distribution ratio decreased with the increase in sulphate ion concentration in the aqueous phase. The extraction equilibrium reaction is suggested as Zn2+aq +1.5 (H2A2)org « [ZnA2.HA]org  +2H+  extraction equilibrium constant (kex) for the above reaction was calculated to be 10-2.26. The extraction process was endothermic in nature having positive DH value of 16.27 kJ/mol. The loading of D2EHPA by Zn(II) is about 4.50 g of Zn(II) by 0.10 M D2EHPA. Possible reaction mechanism has been suggested based on distribution data, extractant concentration and equilibrium pH of the aqueous phase.